2020
DOI: 10.1371/journal.pgen.1008749
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation and gene expression patterns reflect genetic ancestry and environmental differences across the Indonesian archipelago

Abstract: Indonesia is the world's fourth most populous country, host to striking levels of human diversity, regional patterns of admixture, and varying degrees of introgression from both Neanderthals and Denisovans. However, it has been largely excluded from the human genomics sequencing boom of the last decade. To serve as a benchmark dataset of molecular phenotypes across the region, we generated genome-wide CpG methylation and gene expression measurements in over 100 individuals from three locations that capture the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 70 publications
2
48
0
Order By: Relevance
“…To begin validating the potential influence these TFBS-disrupting SNPs might have on their target genes, we focused on a set of 3,996 genes found to be differentially expressed (DE) at a FDR ≤ 0.01% between 19 Korowai individuals, a genetically Papuan population living on the Indonesian side of New Guinea Island, and 48 individuals of Austronesian ancestry sampled in Mentawai, a small island located off the western coast of Sumatra, in western Indonesia, from [41]. These two populations are indicative of the extremes of the cline of Papuan and Denisovan ancestry that is observed across the Indonesian archipelago [5, 42].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To begin validating the potential influence these TFBS-disrupting SNPs might have on their target genes, we focused on a set of 3,996 genes found to be differentially expressed (DE) at a FDR ≤ 0.01% between 19 Korowai individuals, a genetically Papuan population living on the Indonesian side of New Guinea Island, and 48 individuals of Austronesian ancestry sampled in Mentawai, a small island located off the western coast of Sumatra, in western Indonesia, from [41]. These two populations are indicative of the extremes of the cline of Papuan and Denisovan ancestry that is observed across the Indonesian archipelago [5, 42].…”
Section: Resultsmentioning
confidence: 99%
“…We thus asked how many of the genes associated with the GO terms and whose regulation was predicted to be affected by our subset of TFBS-disrupting variants within immune T and B cells were differentially expressed between Mentawai and Korowai in [41]. Overall, we found that 31, 26 and 426 genes predicted to be regulated by Denisovan, Neanderthal and non-archaic TFBS-disrupting variants (31.0%, 22.4% and 26.1% of those associated with all GO terms) were differentially expressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations